Respuesta :

It looks like the equation is

cos(2x) + cos(x) = 0

Use the double angle identity for cosine to write this as

(2 cos²(x) - 1) + cos(x) = 0

2 cos²(x) + cos(x) - 1 = 0

Factorize the left side:

(2 cos(x) - 1) (cos(x) + 1) = 0

Then either

2 cos(x) - 1 = 0   or   cos(x) + 1 = 0

2 cos(x) = 1   or   cos(x) = -1

cos(x) = 1/2   or   cos(x) = -1

[x = cos⁻¹(1/2) + 2nπ   or   x = -cos⁻¹(1/2) + 2nπ]

…   or   [x = cos⁻¹(-1) + 2nπ]

(where n is any integer)

x = π/3 + 2nπ   or   x = -π/3 + 2nπ   or   x = π + 2nπ

We get the following solutions in the interval [0, 2π):

x = π/3   and   x = π   and   x = 5π/3